¿Por qué nos escogió a nosotros para la práctica coral, si somos tan indisciplinados? (2017)
Based on a didactic and pedagogical-musical proposal, this paper reflects on the practice of choir music, starting with the exercise developed with the children from class 5B at Escuela Normal Superior de Popayán, a community that, at a certain point during the school year, was faced with a serious issue of coexistence at school. It was then that Steiner’s eurythmy was used as a methodology for teaching music, which highlighted the importance of learning spaces, play, and movement. From this pedagogical approach, the paper takes a look at its influence on school coexistence and the imaginaries of inner freedom, categories that emerged from the same school context once the information was systematized. The hope is that this work will contribute to the training of music teachers in Colombia, based on pedagogical experiences that, without losing the specificity of teaching, in this case regarding choral practice, establish a connection with the life of children and their problems, with the perspective of a comprehensive education.